Growth phase-dependent biochemical composition of green microalgae: Theoretical considerations for biogas production. (May 2020) - Klin, Marek; Pniewski, Filip; Latała, Adam
Highlights: The discernment of microalgal TMP before BMP tests is recommended. TMP screening allows indication of optimal biomass source: strain and growth phase. Depletion of nutrients is key to learn microalgal full volumetric productivity. Abstract: One of the most efficient and promising technique for biofuel production from microalgae biomass is an anaerobic fermentation. The goal of this work was to investigate changes in the biochemical composition during the long-term cultivation period of 15 green microalgal strains originating from the Baltic Sea. Subsequently, their theoretical methane potential (TMP), which is strictly determined by an algal growth phase and thus physiological state, was established. Based on the full spectrum of changes in the percentage share of lipids, carbohydrates, and proteins in biomass, it was shown that the TMP values differed among strains as well as fluctuated during cultivation. The common trend, i.e., lipids accumulation and proteins breakdown in the late growth phase, was observed for most of the strains; others, however, preferred carbohydrates as storage material. The TMP data obtained herein allows developing a strategy for the design and production of algal biomass biochemically suited for fermentation.